Event Review: 40 years of cooperation between the University of Vienna and MAMUZ - Franz Pieler (EXARC Journal)
The University of Vienna “Practice of Experimental Archaeology” course took place from June 30th to July 3rd at MAMUZ Schloss Asparn/Zaya.